2016
DOI: 10.1038/srep32095
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective levels of IGF-1 exacerbate epileptogenesis after brain injury

Abstract: Exogenous Insulin-Like Growth Factor-1 (IGF-1) is neuroprotective in animal models of brain injury, and has been considered as a potential therapeutic. Akt-mTOR and MAPK are downstream targets of IGF-1 signaling that are activated after brain injury. However, both brain injury and mTOR are linked to epilepsy, raising the possibility that IGF-1 may be epileptogenic. Here, we considered the role of IGF-1 in development of epilepsy after brain injury, using the organotypic hippocampal culture model of post-trauma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 67 publications
0
27
0
4
Order By: Relevance
“…Insulin-like growth factor 1 (IGF-1) is a polypeptide hormone and functions as primary mediator of growth hormone (GH) dependent growth effects in most peripheral tissues (228). In the brain, IGF-1 regulates the proliferation and differentiation of multiple CNS resident cells and has been implicated in several neurological disorders (229)(230)(231). IGF-1 signals through its cognate receptor IGFR-1R, but can also form functional hybrids with the insulin receptor (229).…”
Section: Igfmentioning
confidence: 99%
“…Insulin-like growth factor 1 (IGF-1) is a polypeptide hormone and functions as primary mediator of growth hormone (GH) dependent growth effects in most peripheral tissues (228). In the brain, IGF-1 regulates the proliferation and differentiation of multiple CNS resident cells and has been implicated in several neurological disorders (229)(230)(231). IGF-1 signals through its cognate receptor IGFR-1R, but can also form functional hybrids with the insulin receptor (229).…”
Section: Igfmentioning
confidence: 99%
“…The expression of IGF-1 and IGF-1R is significantly changed after cerebral ischemia injury ( 24 ). Also, some researchers have reported that IGF-1 and IGF-1R, which are expressed in the hippocampus, are associated with the loss of neurons ( 25 , 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…IGF receptor knockout mice demonstrate systemic upregulation of IGF‐1, contributing to the protection of the brain against hypoxic‐ischemic injury . Additionally, a study with posttraumatic epilepsy models showed that IGF‐1 treatment can be beneficial or harmful depending on the stage of the disease . Therefore, it is important to assess serum IGF‐1 levels and their clinical correlations in various neurodegenerative diseases in which IGF signaling and its receptors in the brain are involved .…”
Section: Discussionmentioning
confidence: 99%